2012
DOI: 10.1016/j.jvir.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Suspected Type II Endoleaks in Patients with Enlarging Abdominal Aortic Aneurysms

Abstract: Purpose To evaluate angiographic diagnosis and embolotherapy of patients with enlarging abdominal aortic aneurysms and computed tomographic (CT) diagnosis of type II endoleak. Materials and Methods A retrospective review was performed of all patients referred to a single vascular and interventional radiology section from January 1, 2003, to June 1, 2011, with a diagnosis of enlarging aneurysm and type II endoleak. Twenty-five patients underwent 40 procedures between 12 and 82 months after endograft insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 13 publications
(17 reference statements)
1
29
0
1
Order By: Relevance
“…3 One study included patients with multiple attempts to treat endoleaks including attempts involving coils and Onyx. 4 This study did, however, have six patients where, following failed attempts at other techniques, direct sac puncture and Onyx embolization was employed. These cases are identifiable and have been included.…”
Section: Resultsmentioning
confidence: 98%
“…3 One study included patients with multiple attempts to treat endoleaks including attempts involving coils and Onyx. 4 This study did, however, have six patients where, following failed attempts at other techniques, direct sac puncture and Onyx embolization was employed. These cases are identifiable and have been included.…”
Section: Resultsmentioning
confidence: 98%
“…CT 33 Massis et al 39 2012 Sac expansion ≥ 5 mm within 6 months, sac > 6 cm 4 † n.s. 95 Sheehan et al 40 2004 Persistent leak ≥ 6 months 18 CT 28 Aziz et al 41 2012 Persistent type II endoleak ± sac expansion 23 CT 42 Conrad et al 42 2009 Persistent type II endoleak with sac expansion 35 CT 832 Funaki et al 43 2012 Persistent type II endoleak with sac expansion ≥ 5 mm 27·5 C T 2 5…”
Section: Resultsmentioning
confidence: 99%
“…In addition, no single vessel embolized offered better protection against secondary intervention or sac expansion. One study reported outcomes for both a transarterial approach and direct sac puncture 43 .…”
Section: Overall Outcomes For Interventionsmentioning
confidence: 99%
“…The characteristics that make EVOH copolymer effective in the treatment of cerebrovascular lesions may benefit hemorrhagic lesions elsewhere in the body, and peripheral nonneurologic applications are becoming more accepted (2)(3)(4). Most of the literature on Onyx focuses on neurologic lesions (5,6) and chronic aortic endoleaks (7,8); the remaining literature on the topic largely comprises case reports and case series. In this study, we systematically reviewed the existing literature on the use of EVOH copolymer to treat acute hemorrhage outside of the head and neck to determine its efficacy and safety for use in peripheral lesions.…”
mentioning
confidence: 99%